The Influence of Macromolecular Crowding on HIV-1 Protease Internal Dynamics - Minh, David D.L. (2006)
[Image: see text] High macromolecular concentrations, or crowded conditions, have been shown to affect a wide variety of molecular processes, including diffusion, association and dissociation, and protein folding and stability. Here, we model the effect of macromolecular crowding on the internal dynamics of a protein, HIV-1 protease, using Brownian dynamics simulations. HIV-1 protease possesses a pair of flaps which are postulated to open in the early stages of its catalytic mechanism. Compared to low concentrations, close packed concentrations of repulsive crowding agents are found to significantly reduce the fraction of time that the protease is open. Macromolecular crowding is likely to have a major effect on in vivo enzyme activity, and may play an important regulatory role in the viral life cycle.